Comparison of BCL-2 Ecpression in Periocular Basal Cell Carcinoma Aggressive and Non-Aggressive Types in Mohammad Hoesin Hospital Palembang - Fera Yunita Rodhiaty; Ika Kartika; Ibrahim (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2018)
Abstract Background: Basal cell carcinoma (BCC) is a malignant tumor originating from non- keratinizing cells originating from the basal layer of the epidermis. Basal cell carcinoma is the most common malignant tumor, nearly 90% of all non-melanoma skin cancers. Clinically, BCC is difficult to distinguish, final diagnosis determined based on histopathological examination of complete tumor tissue. Based on histological growth patterns, BCC is divided into two, non- aggressive type (nodular and superficial) and aggressive type (infiltration, micronodular, fibroepithelial, basoskuamosa, keratotic, adnexal differentiation). The examination technique by analyzing the proteins or genes involved is related to the aggressiveness of basal cell carcinoma. Objective: This study was conducted to determine the comparison of expression of Bcl-2 in periocular basal type aggressive and non-aggressive carcinomas in dr. Mohammad Hoesin Palembang. Methodology: A cross sectional analytic study from 26 periocular basal cell carcinoma patients in RSUP dr. Mohammad Hoesin Palembang, January 2014- June 2018. Histopathologic features were examined with hematoxylin-eosine staining and imunohistochemical were examined with Bcl-2 monoclonal antibody. Data were analyzed by bivariate analysis, using chi-square test and fisher exact test. Results: Positive Bcl-2 expression was more common in periocular basal cell carcinoma (93.8%) than aggressive (50%), and nodular type (93.8%) compared to other types of histological differentiation. Positive Bcl-2 expression was also higher in female patients (90.9%) than males (66.7%). There is a significant relationship between expression of Bcl-2 and growth patterns, differentiation of cell histology and also sex of patients with basal cell carcinoma. Conclusion: In this study, there was a significant correlation between expression of Bcl-2 and aggressive and non-aggressive periocular basal cell carcinoma in RSUP dr. Mohammad Hoesin Palembang.